Urgensi Berpikir Kritis Pada Remaja Di Era 4.0 - Williya Novianti (Ma'soem University, 2020)
One of High Order Thinking Skills (HOTS) aspect is critical thinking skills. It is a capital important that students must possess as a provision in facing technological developments and the effects of globalization in the 4.0 era. This study aims to determine the profile of critical thinking skills of adolescents in SMAN 1 Batujajar, especially in class XI IPS in the academic year 2019-2020, which is expected to help students achieve optimal development in the 4.0 era. The research uses a quantitative approach with descriptive methods. The study was conducted at SMAN 1 Batujajar, West Bandung Regency. The selected population was students of class XI of SMAN 1 Batujajar in the academic year 2019-2020. The sampling technique in this study is non probability with homogenous sampling technique, in 162 students of class XI IPS SMAN 1 Batujajar. Data collection uses the form of a test instrument for critical thinking skills. The results showed the profile of critical thinking skills that students are common in middle category, students reasonably skilled in analyzing, evaluating, performing inference and reasoning when engaged in problem solving and decision making. The results of this study can be used as preliminary data for intervention by guidance and counseling teachers or other researchers in developing critical thinking skills, so it is expected to complement and strengthen previous research.